PROTOTIPE PENGUSIR HAMA BURUNG PADA TANAMAN PADI MENGGUNAKAN SENSOR PIR DAN ESP8266 DI KELURAHAN MATEKKO KABUPATEN BULUKUMBA - Durratun Nasiha Firman; Farida; Andi Nurul Faizah (Institut Teknologi dan Bisnis Bina Adinata, 2023)
Abstrak –This study aims to: (1) Design a prototype of Bird Pest Repellent on Rice Plants Using PIR and ESP8266 Sensors in Matekko Bulukumba Village. (2) Knowing the implementation of the prototype of Bird Pest Repellent on Rice Plants Using PIR and ESP8266 Sensors in Matekko Bulukumba Village. This study uses a prototype research method where the stages are as include collection of needs, make prototype, prototype evaluation, encoding system, System testing, System evaluation & Using the system. Based on the results of this study, it can be concluded that: (1) The prototype of Bird Pest Repellent on Rice Plants was designed using 3 components, namely 3 PIR (Passive Infra Red) Sensors, 1 Esp8266 and 3 Servo Motors. This prototype of Bird Pest Repellent on Rice Plants uses a plywood board as a place to place the components of the tool which has a width of 47 centimeters and a length of 50 centimeters. The PIR (Passive Infra Red) sensor will be placed at the end of each square-shaped plywood board. ESP8266 will be placed in the middle of the Servo Motor and the Servo Motor will be placed at the end of the upper plywood board. (2) The implementation of the bird repellent prototype on rice plants is able to detect the presence (bird pests) by means of a servo motor moves the rope and provides notifications to the blynk application.